Impact of Broken Family Status to Values Education in Relation to their Personality Development.: Vol.3, No.2 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The primary goal of this research is to determine Impact of Broken Family Status to Values Education in Relation to their Personality Development. A broken family is one that has an unhealthy or severed relationship within the family unit. Families that have broken down are a major social issue that must be addressed. This study will help to give awareness to students.This study utilized the descriptive method design for the investigation in collecting information about the Impact of Broken Family Status to Values Education in Relation to their Personality Development. Through the process of purposive sampling, a total number of 30 students were selected to participate in the study. The major instruments used for gathering data was a survey questionnaire. The data gathered were analyzed using percentages and weighted mean. The survey results show that most of the respondents were female between the ages of 20 and 25. The third year had the highest number of respondents across all year levels. Most of the respondents have a monthly family income of P 9,999.00 and below. In terms of the respondents' personality development, self-esteem, with a numerical interpretation of 3.52, was ranked as the most important characteristic that may influence personality development among respondents from broken families. As to the emotional problems, with a numerical interpretation of 3.51, adults are more likely to experience emotional problems in families where the parents' marriages have failed or where there is a lack of affection. As to the effects of broken family status on the student’s Mental health with a numerical interpretation of 3.55 it appears that having a broken family has the greatest negative impact on a student's mental health. As to Physical abuse with a numerical interpretation of 3.5 showed that the students' families have been destroyed due to physical abuse. One of the most terrible aspects of family life is how adult who witness, or experience physical violence are affected.The researchers see the real problem that occurred in each of the respondents' situations, and there is a need for attention and guidance to those who are facing this type of problem. In this manner, the problem will arise; a broken family can have a negative impact on all domains of the child’s development, including personal development. To minimize the negative effects of broken families, the researchers prepared a set of guidelines, i.e., to improve relationships inside the family and at home, consider family counseling; maintain strong family bonds through open communication in which each family member may openly express their thoughts with regard to one another; build and keep up a positive working atmosphere; relationships within the family that are loving and harmonious; and spend time together and reassure the family members that they are all cherished.